Pengaruh, Modal Kerja, Ukuran Perusahaan, Struktur Modal, dan Pertumbuhan Perusahaan, terhadap Profitabilitas Perusahaan - Mochammad Rifqi Rabani; Mahroji (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The profitability of a company, measured through Return On Assets (ROA), indicates the company's ability to effectively generate profits from its asset utilization. This research aims to investigate the impact of working capital, firm size, capital structure, and firm growth on profitability. In this study, 12 companies were selected using purposive sampling method, and a total of 60 objects studied were profitable companies during the period from 2019 to 2022. Secondary data in the form of financial reports obtained from the website www.idx.co.id were used. Regression analysis using SPSS software was employed to measure the data. The results of the study indicate that working capital, firm size, and capital structure have a significant influence on profitability, while firm growth does not. The Adjusted R Square value demonstrates that working capital, firm size, capital structure, and firm growth explain a substantial portion of the variation in profitability, while the remaining portion is influenced by other factors beyond the scope of this study. A strong profitability of a company will instill trust from the public and investors to invest in the company.